THE GENUS MURRAYA (RUTACEAE) IN JAVA - Inggit Puji Astuti; Rugayah Rugayah; Ratna Susandarini; Purnomo Purnomo (PTTI, 2011)
The genus Murraya consists of 11 species in the world. Based on herbarium specimens and living collections from Bogor, Cibodas, and Purwodadi Botanical Gardens, Yogyakarta, and Malang, there are 4 species of Murraya in Java, namely M. crenulata, M. exotica, M. koenigii and M. paniculata. Key to species and other informations of the species were presented.